Trajetórias de professoras negras : vida escolar e profissão - Leite, Carmen Cinira Siqueira (2006)
This study is about the life stories of black teacher women. The objective is concerned with school and family background of black teachers from Cuiabá Education Secretariat. It was necessary to understand what they have been living since they started their school life until they have become teachers. The challenges these teachers faced reveal what it is to be a black teacher in a racist, sexist society and the way they have constructed their racial, feminine, professional identity and achieved their goals. It was used qualitative methodology and to collect data, it was adopted the technique of life story. Although there are different stories, at a particular point, the stories reveal that the black teachers had persistence and self-determination to overcome the difficulties during school process until becoming teachers. The narratives provide clues about the existence of autonomy at workplace. On the other hand, it´s possible to notice the strategies found to avoid situations with racial and gender discrimination. To achieve the project of beeing a teacher; family appears in the reports as one that provides moral, emotional, symbolic and financial support. therefore, giving black women the opportunity to speak out, implies giving visibility to this people who were silent by history. The number of black women who have achieved visibility and social mobility through education is still very low.